Evaluation of Activity of Phospholipids in Blood Coagulation in Vitro - Silver, M. J; Turner, D. L; Rodalewicz, I; Giordano, N; Holburn, R; Herb, S. F; Luddy, Francis E (Thrombosis and Haemostasis, 1963)
1. The effects of phospholipids, solubilized by different methods in different clotting tests are presented.2. Complete fatty acid analysis of a phosphatidylserine fraction from beef brain is given.3. Data relating electric charge of phospholipid particles to activity in clotting are presented.4. A critical discussion of the factors which influence the activity of phospholipids in blood clotting terminates the paper.